Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$\begin{align} u(x_1x_2) & = -a\ln{a\over (a+b)x_1} -b\ln {b\over (a+b)x_2} \\ & = a\ln x_1 + b\ln x_2 + \text{constant}. \end{align}$$

Could somebody please explain how this is simplified? I'm confused with the steps needed to give us these signs.

(Image of original formula as supplied by OP)

share|improve this question
add comment

2 Answers 2

up vote 4 down vote accepted

$$u(x_1,x_2) = -a(\ln a - \ln(a+b)x_1) - b(\ln b - \ln(a+b)x_2) =$$

$$ =-a\ln a + a\ln(a+b)x_1 -b\ln b + b\ln(a+b)x_2 =$$

$$= -a\ln a -b\ln b + a\ln(a+b) +a\ln x_1 +b\ln(a+b) + b\ln x_2 = b\ln x_1 + b\ln x_2 + C$$

where

$$C = -a\ln a -b\ln b + (a+b)\ln(a+b)$$

share|improve this answer
    
Try using \log or \ln between signs of dollars to properly write the above –  DonAntonio Oct 15 '12 at 3:43
    
Im sorry. forgot about this! Thanks –  Chasky Oct 15 '12 at 4:03
add comment

Recall the following identities $$\ln(pq) = \ln(p) + \ln(q)$$ $$\ln \left( \dfrac1q \right) = - \ln(q)$$ $$\ln \left( \dfrac{p}{q} \right) = \ln(p) - \ln(q)$$ Make use of the above identities to get your answer.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.